Deteksi Alfabet Bisindo Menggunakan Mediapipe Holistic Secara Real-Time - Dani Pradana Kartaputra; Herna Gunawan; Asri Eka Lestari (LPPM STMIK Bandung, 2023)
The resulting system will detect and classify gestures or movements that speak the B language contained in it directly using a holistic mediapipe to detect the skeleton on the hands, body, and face and use a landmark model of poses, faces and each to generate a total of 543 landmarks. (33 pose landmarks, 468 facial landmarks, and 21 hand landmarks).